TRAINING TO BUILD PERSONAL BRANDING ON LINKEDIN SOCIAL MEDIA TO HANDLE EDUCATED UNEMPLOYMENT RATES AT HIGHER COLLEGE LEVEL - Mayasari, Endah; Irdhayanti, Efa; Syahputri, Anggraini (CV. Alina, 2024)
The number of unemployed in Indonesia according to the Central Statistics Agency as of August 2023 at the tertiary level has increased. Technology is developing rapidly and the emergence of new jobs, a combination of macro trends and technology adoption is causing the disappearance of a number of types of jobs. Students as one of the keys to the nation's success are required to have a high level of productivity, especially for those who are starting a career. The aim of this Community Service activity in the form of training is to build students' personal branding with Linkedin to prepare them for careers using Linkedin social media to anticipate the number of educated unemployed at the tertiary level. The method used is Participatory Action Research through the stages of problem identification, implementation and evaluation. Participants in this training numbered 90 students. The results show that the participants gained new knowledge and skills to prepare for a career and this is one solution in facing the challenges of technological disruption by using social media Linkedin.